FAKTOR DOMINAN KESULITAN MAHASISWA PADA PENULISAN SKRIPSI - Rahma Faelasofi (Universitas Muhammadiyah Pringsewu, 2018)
Abstract   Graduation on time is the goal of every student. However, in reality there are obstacles in completing the study in time. One of the causes is the time consuming in writing of thesis which can take more than one year, whereas ideally writing thesis is 6 months. The purpose of this study is to determine the factors of student difficulties in writing thesis. The populations in this study are students who are writing thesis more than one year on mathematics education department in the academic year 2016-2017. The statistical test used is multivariate analysis to find the dominant factor from seven factors that are suspected to be the cause of the student difficulties in writing thesis. The results of this study obtained that motivation becomes the dominant factor which becomes the student constraint in writing thesis. Keywords: difficulty  factors in writing thesis, motivation  factor, time in writing thesis